Taxonomic revision of the Apiomerus maya species group (Heteroptera: Reduviidae: Harpactorinae) - Masonick, Paul; Weirauch, Christiane (Zootaxa, 2022)
The Apiomerus maya species group of the genus Apiomerus Hahn, 1831 (Hemiptera: Heteroptera: Reduviidae: Harpactorinae: Apiomerini), the bee assassins, is revised. Four species that are native to parts of Mexico and Central America are recognized and redescribed: Apiomerus maya Dispons, 1971, A. pipil Dispons, 1971, A. venosus Stål, 1872, and A. immundus Bergroth, 1898. Intraspecific polychromatism and male genital morphology are documented for the group. The taxonomy of two previously recognized species is updated: A. tristis Champion, 1899 syn. nov. is here synonymized with A. venosus and A. guatemalensis Dispons, 1971 syn. nov. with A. pipil.